The Effect Of The Tetrapreneur Model On The Sustainability Of BUMDes With University Partnership As A Moderating Variable - Puspita, Ni Komang Irma; Adiputra, I Made Pradana; Diatmika, I Putu Gede (SEAN Institute, 2024)
This study was conducted to test the Influence of the Tetrapreneur Model on the Sustainability of BUMDes with Higher Education Partnerships as a Moderation Variable. The population in this study is 129 villages in Buleleng Regency with a sample of 93 villages out of 129 villages calculated using the purposive sampling formula. The respondents in this study were the head of BUMDes, members of BUMDes and Village Heads. Data analysis used SEM-PLS Version 3 with a total of 85 respondents who filled out the questionnaire. The results of the study show that the tetrapreneur model has a positive and significant effect on the sustainability of BUMDes. Higher education partnerships significantly moderate the influence of the tetrapreneur model on the sustainability of BUMDes.